Caracterização da logística de distribuição de hortaliças orgânicas na cidade de São Paulo - Terrazzan, Priscila (Universidade Federal de São Carlos, 2009)
Organic production plays a key role in agro-social development, and in commercialization, distributors are of essential importance for the supply to the sale points of organic products. In that way, this dissertation investigates the key factors of the logistics of distribution of organic horticultural products in the city of São Paulo. The research was developed between April and October 2008, when were interviewed the representatives of supermarkets and of the distribution companies of organic products. Qualitatively, the work was done through the theoretical review, construction of forms and inferences on the information given by interviewees. The quantitative stage was the application form and the analysis and relations of data, to identify particularly: main actors representative of the distribution chain and their characteristics, how the management of logistics activity is done, the level of performance of distribution system. The result showed that these distribution systems, satisfy, in part, to technological and operational requirements for the supply to the supermarket. Three major groups represent the supermarket sector and their supply is basically made by eleven distribution companies, eight of which participated in the survey and provide an average of 1,187,000 units of fruit and vegetables per month. Supermarkets absorb 89% of the total sold by distributors. The performance of the distribution system is a little short of satisfying the supermarket, requiring better techniques for handling and transport. The distributors are going professional on the corporate planning and to work with the integration of the sectors of the company, which will require an optimization of its processes of operation and management. In this sense, they search for work with the development of the supply chain. Logistics activities are little measured and there is a low efficiency in carrying capacity of vehicles (the overall average is 77.5%). The availability of load return is less than 50%, and the cost of transport represents an average of 11.88% of sales of these distributors. The logistical successful arrangements may serve as a reference to the benchmarking of agents of the organic sector to the improvement of its logistics distribution.
Characterization of distribution logistics of organic horticultural products in São Paulo city
Keywords: Agricultura orgânica; Comercialização; Distribuição de mercadoria; Gerenciamento de distribuição; Hortaliças; CIENCIAS AGRARIAS